The strategy-focused organization : how balanced scorecard companies thrive in the new business environment - Kaplan, Robert S. 4 0 16; 1941- Norton, David P.; 5 (Boston, Massachusetts : Harvard Business School Press, 2001)
Robert Kaplan and David Norton share the results of ten years of research into more than two hundred companies who have implemented the Balanced Scorecard system, revealing how the scorecard can help companies create new performance management frameworks that focus on effective strategy.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Strategic planning. -- 20; 20; 2